2013
DOI: 10.1115/1.4025395
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of Compression Molded Aspherical Glass Lenses

Abstract: Residual stresses and refractive index of molded glass lenses are important quality indicators of their optical performance. In this research, the control of residual stresses and refractive index variation of molded glass lenses were experimentally investigated by postmolding annealing. Residual stresses were quantitatively measured using a circular polariscope. Refractive index was reconstructed and calculated by an optical setup based on Mach-Zehnder interferometer. In addition, geometry of the aspherical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the peripheral region, larger Δ Z is found in the range of −3.52 to 4.96 µm, but is still below the pixel dimension of 7.1 µm and the layer thickness of 5 µm. The experimentally measured manufacturing accuracy is comparable with conventional methods for fabricating aspheric lenses . Therefore, the ultrasmooth optical surface together with the subvoxel precision of surfaces make it possible for the rapid 3D printing of high‐quality optical lenses.…”
mentioning
confidence: 70%
“…In the peripheral region, larger Δ Z is found in the range of −3.52 to 4.96 µm, but is still below the pixel dimension of 7.1 µm and the layer thickness of 5 µm. The experimentally measured manufacturing accuracy is comparable with conventional methods for fabricating aspheric lenses . Therefore, the ultrasmooth optical surface together with the subvoxel precision of surfaces make it possible for the rapid 3D printing of high‐quality optical lenses.…”
mentioning
confidence: 70%
“…Given the complexity of interface friction and glass material properties, finite element analysis is an effective alternative to analyze the glass molding process [29][30][31][32][33] and evaluate the friction coefficient. 10,12 In this paper, FEA models were developed to predict the axial displacement history and sample's final dimensions when different friction coefficient values were used.…”
Section: B Finite Element Analysis Resultsmentioning
confidence: 99%
“…The simulation results indicated that the liquid thermal expansion coefficient had a great influence on the predicted refractive index change of the lens and the residual stress distribution. Tao [18] clarified that the annealing process significantly affects the refractive index, residual stress distribution, and shape of the lens. Pallicity et al [19] used the photoelasticity of the glass to measure the residual birefringence of the formed lens by a six-step phase shift method after considering the stress relaxation, structural relaxation characteristics, and friction characteristics.…”
Section: Introductionmentioning
confidence: 99%